Relationship between gut microbiota and markers of myocardial fibrosis in with chronic heart failure with preserved ejection fraction - A. N. Kaburova; O. M. Drapkina; S. M. Yudin; S. N. Koretsky; V. V. Makarov; M. S. Pokrovskaya; S. A. Kraevoy; B. B. Shoybonov; I. A. Efimova (Кардиоваскулярная терапия и профилактика)
Aim. To study the relationship of gut microbiota (GM) with serum myocardial fibrosis markers in patients with heart failure with preserved ejection fraction (HFpEF).Material and methods. The composition of the gut microbiota among 42 patients with HFpEF aged 67,0 [64,0; 71,5] years (men, 57,1%) was assessed by 16S ribosomal ribonucleic acid sequencing. The quantitative determination of myocardial fibrosis markers was carried out by enzyme-linked immunosorbent assay. Correlation and multivariate regression analysis of relationships between the relative abundance of intestinal bacteria and the concentration of the procollagen type I carboxy-terminal propeptide (PICP) and N-terminal propeptide of procollagen type III (PIIINP) was carried out.Results. The PICP and PIIINP concentrations were 918,0 [700,0; 1032,8] pg/ml and 6,2±2,7 pg/ml, respectively. Correlation analysis revealed a direct relationship between the relative abundance of Allisonella and PICP (r=0,32), as well as Blautia, Enterobаcteriaceae (unclassified) and PIIINP (r=0,37 and r=0,32), p<0,05. The inverse relationship was determined for the relative abundance of the genera Ruminococcus (r=-0,37), Ruminococcaceae (unclassified) (r=-0,31), Gemmiger (r=(-0,35) and PICP, as well as Bilophila and PIIICP (r=(-0,34). Multivariate regression found (normalized coefficient in parentheses) that the abundance of Butyricimonas (0,27) и Blautia (0,35) was directly related to the PICP levels, while the abundance of the genus Intestinimonas ((-0,23) showed an inverse association with the marker level. The abundance of most genera had an inverse relationship with PIIINP: Atopobium (-0,25), Cellulosilyticum (-0,31), Solobacterium (-0,32), Turicibacter (-0,47), Bilophila (-0,30). The directness of the association with  PIIINP concentration was demonstrated for the relative abundance of Paraprevotella (0,32) и Desulfovibrio (0,28). The p-value for all associations is <0,05.Conclusion. The relative abundance of GM genera in patients with HFpEF is associated with fibrosis markers (PICP and PIIINP). The results obtained make it possible to deepen the understanding of the relationship between GM and pathogenesis of HFpEF, which may become a step towards understanding the GM role in the progression of left ventricular diastolic dysfunction and rationale for future studies.